1932
DOI: 10.1002/andp.19324050405
|View full text |Cite
|
Sign up to set email alerts
|

Elektronenbeugung und Molekülbau. II

Abstract: Elektronenbeugung wn d M o leku 1 Ir au,. I I Pow R. W i e r k (Xlit 23 I'ignrcn) l n h a i t : 1. Grundlagen uiicl Ziel. -a 2. Esperimenteile Erginzungen. -3. Studien uber Kohlenwasserstoffe. -4. Fragen der Isomerie und der freien Drehbsrkeit. -.5. Bemerkung zur \Tinkeluiig am Sauerstoffatom. -Zusammenfassung. NrtturwisseIlsc1i:iftell 1% S. 205. 1930. 2 ) Ann. cl. I'hys. [5] 9. S. 521. 1931. (I). 454 AnnalPn der Physik. 5. Folge. Band 13. 1932 durcli die Elektronenhiille iii einfacher Weise Rechiiung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1933
1933
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…So Morino made his first GED work with him by modifying the apparatus for measurement of the diffraction halos of gas-phase dichloroethane [19]. As already reported by Wierl [10,11] and Beach/Palmer [20], it was easily confirmed that the trans form was the main conformer in the vapor. In addition, the presence of the cis form was excluded, and the diffraction pattern, especially the feature of a weak peak at s ∼ = 6.0Å −1 , supported the suggestions from the dipole moment, Raman, and theoretical studies that about 20% gauche form was present at room temperature.…”
Section: Yamaguchi and Morinomentioning
confidence: 56%
See 3 more Smart Citations
“…So Morino made his first GED work with him by modifying the apparatus for measurement of the diffraction halos of gas-phase dichloroethane [19]. As already reported by Wierl [10,11] and Beach/Palmer [20], it was easily confirmed that the trans form was the main conformer in the vapor. In addition, the presence of the cis form was excluded, and the diffraction pattern, especially the feature of a weak peak at s ∼ = 6.0Å −1 , supported the suggestions from the dipole moment, Raman, and theoretical studies that about 20% gauche form was present at room temperature.…”
Section: Yamaguchi and Morinomentioning
confidence: 56%
“…There they remarked: "Es scheinen zwei Gleichgewichtslagen vorzuliegen, die einer cis-und translage entsprechen." In the lovely GED papers of Wierl [10,11], he observed the Cl· · ·Cl distances in ClH 2 C CH 2 Cl at 3.2 ± 0.1 and 4.4 ± 0.1Å, and he interpreted them as the cis and trans forms, respectively. His assignment was rather surprising, however, because he had correctly calculated the dependence of the Cl· · ·Cl distance on the angle of internal rotation and displayed it in a diagram [11].…”
Section: Mizushima's Visit To Debyementioning
confidence: 98%
See 2 more Smart Citations
“…In a normal paraffin chain the binding forces between the carbon atoms of the chain can be assumed to be practically constant. Wierl (42) has measured the distances in Angstrom units between the carbon atoms in a chain by his method of electron rays, as follows: ethane, C2H6,1.52 ± 0.1; propane, CsHs, 1.52 ± 0.05; butane, C4H10, 1.52 ± 0.05; pentane, C6Hi2, 1.53 ± 0.05; hexane, C6Hi4, 1.54 ± 0.05. Investigations with Rontgenrays have shown that the dimensional increase of the elementary compound per CH2 group in a series of homologous paraffins is completely constant, the value of this distance being 1.54 A. U.…”
Section: IVmentioning
confidence: 99%